Global prevalence of macrolide-resistant Staphylococcus spp.: a comprehensive systematic review and meta-analysis - Navidifar, Tahereh; Zare Banadkouki, Abbas; Parvizi, Elnaz; Mofid, Maryam; Golab, Narges; Beig, Masoumeh; Sholeh, Mohammad (Frontiers in Microbiology, 2025)
BackgroundStaphylococcus is a genus of bacteria responsible for various infections ranging from mild skin to severe systemic diseases. Methicillin-resistant Staphylococcus aureus (MRSA) and coagulase-negative staphylococci (CoNS) are significant challenges owing to their resistance to multiple antibiotics, including macrolides, such as erythromycin, clarithromycin, and azithromycin.ObjectiveThis study aimed to systematically review and synthesize data on the prevalence of macrolide resistance in Staphylococcus spp., identify trends and changes in resistance patterns over time, and assess how testing methods and guidelines affect reported resistance rates.MethodsThe study conducted a systematic search of the Scopus, PubMed, Web of Science, and EMBASE databases. Studies have reported the proportion of macrolide-resistant Staphylococcus spp. Two authors independently extracted and analyzed the data using a random-effects model. Heterogeneity was assessed, and subgroup analyses were performed based on country, continent, species, AST guidelines, methods, and period.ResultsIn total, 223 studies from 76 countries were included. The pooled prevalence of resistance to erythromycin, clarithromycin, and azithromycin were 57.3, 52.6, and 57.9%, respectively. Significant heterogeneity was observed across studies (I2 > 95%, p < 0.001). Oceania (72%) had the highest erythromycin resistance, whereas Europe had the lowest (40.7%). Subgroup analyses revealed variations in resistance based on the species, with higher resistance in MRSA than in MSSA and CoNS than in other species. Over time, a slight decrease in erythromycin resistance has been observed (59.6% from 2015–2019 to 55% from 2020–2023).ConclusionThis study emphasizes the high prevalence of macrolide resistance in Staphylococcus spp. and its notable regional variation. These findings highlight the necessity for standardized methodologies and global surveillance to manage macrolide resistance effectively. Controlling antibiotic resistance should prioritize enhancing public health measures and updating treatment guidelines.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=557756, CRD42024557756.